Factors influencing the implementation of local economic development policy in Gert Sibande district municipality, South Africa - Mashinini, Ignatia Nonhle (My University, 2017)
The assessment of factors that affect the implementation of Local Economic Development (LED) policy at local government level remains critical. Factors such as institutional arrangements and institutional capacity contribute largely to the outcomes of policy in the public sector. The purpose of this research was to establish the functional role of the institutional arrangements and institutional capacity that are in place for enhancing LED policy outcomes in Gert Sibande District Municipality in Mpumalanga. In South Africa, similar to other democratic societies, the outcome level of performance of LED demonstrates government’s commitment to and ability in ensuring better living standards, including the education and health of the people. The objectives of the study were to investigate the effectiveness of the institutional arrangements and institutional capacity for implementation of LED policy outcomes. Secondly, the study aimed at establishing the nature of institutional and operational structures for LED. Lastly, the study examined the institutional capacity for LED implementation. The research involved undertaking a comprehensive literature review, and developing an appropriate theoretical framework. A desktop study was conducted to identify factors that affect the implementation of LED policy in the GSDM. They are two major theories, namely the reformist paradigm and the new institutionalism theory that underpin this research. A case study design was more ideal for this study because the it seeks to establish a holistic and in-depth investigation of the institutional arrangements and associated institutional capacity of the lead institution for LED in GSDM. The case study research design has provided an opportunity to establish a detailed understanding of the institutional arrangements which relate to institutional capability to implement and achieve the outcomes of LED policy. Data was collected using a semi structured interview guide amongst employees and political members of GSDM, and provincial and national representatives who are responsible for supporting municipalities on LED. A desktop analysis on documented performance reports was also undertaken as a secondary data source to triangulate primary data. Theories of local economic development such as the reformist paradigm or alternative developmental approaches to local economic development and new institutionalism were used to analyse the findings and map the analytical conclusions. One of the major findings of this study is that the current institutional arrangements for GSDM are weak; as a result, they do not fully support the implementation of the LED policy. The new institutionalism theory argues that public institutions should produce a conducive environment through creating policies and legislation that eliminate the barriers to growth Secondly, the research finds that the institutional capacity and capability to implement efficient and effective LED policy remains a challenge due to a number of factors, namely (a) a low skills base in the LED unit; (b) the high vacancy rate such that critical positions remain unfilled in the planning and economic development department; (c) inability and lack of capacity to manage LED structures and enhance involvement of partnerships in LED; (d) the majority of LED policy outputs since 2007 to 2012 were not achieved due to institutional capacity challenges, and (e) the funding model for municipalities remains a challenge. Thus, GSDM is characterised as a rural municipality with limited resources for economic growth and development as well as having serious capacity and development challenges. 6 These institutional capacity challenges have contributed to the high unemployment rate, widening inequalities, low levels of economic development, poor policy implementation, low performance at an institutional level and lack of compliance with legislation due to weak business systems. On the other hand, LED emphasizes strong reliance on local resources, leadership, and institutions to respond to local economic crises and opportunities. It has been argued that rural economies require more attention as the economic and social challenges tend to be more complicated compared to urban economies due to the low skills of the labour force. In addition, rural economies tend to rely more on primary economic sectors such as agriculture, and mining social transfers from government. One of the key recommendations made in this study is that the GSDM needs to ensure that the district LED development agency is established to facilitate, coordinate and implement LED policy initiatives. In addition, the LED development agency needs to be adequately capacitated with requisite skills in order to deal with institutional capacity challenges and also to ensure that the partnership between stakeholders and civil society is strengthened in the implementation of LED. This will enhance local economic growth and development, create more job opportunities and result in efficient public involvement in the LED process. Secondly, the GSDM in partnership with stakeholders in the public sector, needs to develop short, medium and long-term strategies to address the low skills base, and the scarce and critical skills shortages in the district. Lastly, the research also recommends that GSDM needs to review the current organisational structure in order to improve the implementation of organisational policies, enhance service delivery and realise the developmental mandate of local municipalities as articulated in the constitution of the country. This research should be expanded to include the other district municipalities in the Mpumalanga province in order to get a broader picture of local government capability to implement public policy and assess factors that impede the implementation of LED policy. It is imperative to note that due to the short duration of this study and the unavailability of the employees of GSDM, national and provincial departments, and members of the LED forums, limited information was collected in this regard. Thus the findings of this study cannot be generalised due to its limited scope yet it hopefully provides a meaningful understanding of the capability of public institutions at the local level to implement public policies within the South African context.
Research Dissertation submitted and meets the requirements for the Master’s Degree in Public Policy
Keywords: Economic development projects; Community development--South Africa